(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Turbo codes are error correction codes that are widely used in communication systems. Turbo codes exhibits high error correction capability as compared with other error correction codes. This paper proposes Very Large-Scale Integration (VLSI) architecture for the implementation of Turbo decoder. Soft-in-soft out decoders, interleavers and deinterleavers is used in the decoder side which employs Maximum-a-Posteriori (MAP) algorithm. The number of iterations required to decode the information bits being transmitted is reduced using MAP algorithm. For the encoder part, this paper uses a system which contains two Recursive convolutional encoders along with pseudorandom interleaver in encoder side.